Inégalités sociales et représentations de l’enfant dans Cartucho de Nellie Campobello et Balún-Canán de Rosario Castellanos - Sarah Diraison (IdeAs)
Representations of ‘pure and innocent ideal children’ started in literature in the 19th century. They embody a moral ideal to which contemporary child characters in novels continue to be compared. Academic studies of ideal representations of children in novels tend to consider only the geographic and chronological contexts, while sidelining the importance of social inequalities. This article reflects on how children were perceived and on the moral values that society assigned them. It focuses on the Mexican novels Cartucho (1931) by Nellie Campobello and Balún-Canán (1957) by Rosario Castellanos. Both works use little girls as narrators and are highly inspired by the authors’ childhoods, but these novels take place in very contrasting social contexts, revealing the inequalities of childhood status in the mid-twentieth century. Consequently, this article considers the inequalities between the authors’ childhoods as an analytical tool to observe how this ideal is reflected in fiction, particularly when the narrators are confronted with violence. The main finding is that representations of little girls facing violence are much more unsentimental when written by authors that grew up in precarious conditions, such as Nellie Campobello. This representation in Cartucho was considered amoral and had a significant impact on its reception, marginalizing the novel until the representation of children evolved in the 21st century.